Non-dermatoscopic image analysis for the recognition of malignant skin diseases with convolutional neural network and autoencoders - Coronado R. (2018)
This work has been partially funded by the Master Scholarship at the Universidad Nacional de San Agustín, which is an initiative of CITEC through a fund FONDECYT (Perú). We would like to thank research department of Instituto Nacional de Enfermedades Neoplásicas from Peru, for gently providing us his advice on the direction of this article.